Plant and Fungal Genome Editing to Enhance Plant Disease Resistance Using the CRISPR/Cas9 System - Paul, Narayan Chandra; Park, Sung-Won; Liu, Haifeng; Choi, Sungyu; Ma, Jihyeon; MacCready, Joshua S.; Chilvers, Martin I.; Sang, Hyunkyu (Frontiers in Plant Science, 2021)
Crop production has been substantially reduced by devastating fungal and oomycete pathogens, and these pathogens continue to threaten global food security. Although chemical and cultural controls have been used for crop protection, these involve continuous costs and time and fungicide resistance among plant pathogens has been increasingly reported. The most efficient way to protect crops from plant pathogens is the cultivation of disease-resistant cultivars. However, traditional breeding approaches are laborious and time intensive. Recent development of the CRISPR/Cas9 system has enhanced disease resistance among different crops such as rice, cacao, wheat, tomato, and grape. This system allows for precise genome editing of various organisms via RNA-guided DNA endonuclease activity. Besides genome editing in crops, editing the genomes of fungal and oomycete pathogens can also uncover new strategies for plant disease management. The present review focuses on the recent studies of plant disease resistance against fungal and oomycete pathogens using the CRISPR/Cas9 system. For long-term plant disease management, the targeting of multiple plant disease resistance mechanisms with CRISPR/Cas9 and insights gained by probing fungal and oomycete genomes with this system will be powerful approaches.